Walt Whitman & the world - Allen, Gay Wilson, 1903-1995.; Folsom, Ed, 1947- (Iowa City, Iowa : University of Iowa Press, 1995)
Celebrating the various ethnic traditions that melded to create what we now call American literature, Whitman did his best to encourage an international reaction to his work. But even he would have been startled by the multitude of ways in which his call has been answered. By tracking this wholehearted international response and reconceptualizing American literature, Walt Whitman and the World demonstrates how various cultures have appropriated an American writer who ceases to sound quite so narrowly American when he is read into other cultures' traditions.
Introduction: "Salut au Monde!" / Ed Folsom and Gay Wilson Allen -- Whitman in the British Isles / M. Wynn Thomas. Charles Ollier (1856). Anonymous Review (1856). Edmund Ollier (1856). Matthew Arnold (1866). William Michael Rossetti (1868). Anne Gilchrist (1870). Algernon Charles Swinburne (1872). George Saintsbury (1874). Edward Dowden (1878). Gerard Manley Hopkins (1882). John Robertson (1884). John Robertson [epigraphs] (1884). Ernest Rhys (1885). Roden Noel (1886). Anonymous Review (1886). Havelock Ellis (1890). R.W. Raper (1890). Pauline W. Roose (1892). W.B. Yeats (1892, 1894). John Addington Symonds (1893). Henry Salt (1894). Edmund Gosse (1896). J.A. MacCulloch (1899). G.K. Chesterton (1904). W.T. Hawkins (1906). E.M. Forster (1911). D.H. Lawrence (1913). Basil de Selincourt (1914). P. Mansell Jones (1914). John Cowper Powys (1915). Padraic Colum (1919). Hugh I'Anson Faussett (1942). V.S. Pritchett (1946). J. Middleton Murry (1955). David Daiches (1956).
Includes bibliographical references (pages 437-466).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Whitman, Walt, -- 1819-1892 -- Criticism and interpretation -- History; Whitman, Walt, -- 1819-1892 -- Appreciation -- Foreign countries; Whitman, Walt, -- 1819-1892; American literature -- Appreciation -- Foreign countries; National characteristics in literature; Littérature américaine -- Appréciation -- Pays étrangers.; Caractéristiques nationales dans la littérature.; LITERARY CRITICISM -- Poetry; American literature -- Appreciation -- Foreign countries; Art appreciation; National characteristics in literature; Criticism, interpretation, etc; History